The Destruction of the Anaerobic Environment Caused by Rumen Fistula Surgery Leads to Differences in the Rumen Microbial Diversity and Function of Sheep - Cao, Yurong; Zhu, Baozhen; Li, Fei; Zhang, Duihong; Guo, Tongqing; Li, Fadi; Yang, Guo (Frontiers in Veterinary Science, 2021)
This experiment was to study the impact of rumen fistula surgery on the rumen microbios in sheep. Six male adult Hu sheep (48.8±0.23 kg, 0.5 years) were fed at 0700 and 1800 with ad libitum access to water. The rumen fistula was installed in the same batch at 0600 from 0900. Monitoring the dry mater intake and the output of dry mater faces 1, 2, 4, 6, 8, 10, 12, 14 days after fistulated surgery. The collection of rumen fluid was arranged at 1d during rumen surgery (DRS1), 3d after rumen surgery (ARS3) and 14d after rumen surgery (ARS14) for volatile fatty acid (VFA) and DNA extraction for sequencing and bioinformatics Analysis. There was no difference in DMI, the pH apparent digestibility of dry matter, organic matter, neutral detergent fiber, acid detergent fiber both before and 14 days after surgery. Increases were observed in the acetate and total VFA at ARS3. There was no difference in digestion of dry material, organic material, neutral detergent fiber, and acid detergent fiber before and after surgery. The relative abundance of Bacteroides decreased from 61.96% at DRS1 to 28.85% at ARS3. In comparison with the DRS1 and ARS3, the relative abundance of Firmicutes in the ARS14 increased to 44.58% (P < 0.01). Proteobacteria increased from 11.33% at DRS1 to 51.66% at ARS3 and then decreased to 11.39% at ARS14. Prevotella decreased form 61.06% at DRS1 to 28.04% in the ARS3. Succinivibrio increased from 8.32% at DRS1 to 48.58% at ARS3, but decreased to 10.43% in the ARS14. Compared with DRS1 and ARS3, the ARS14 was in higher Simpson and Shannon index. As for the BugBase function prediction, rumen fistula surgery increased the microorganism abundance of aerobic and facultative anaerobic phenotype, and anaerobic phenotype decreased in the ARS3. Higher microorganism abundance of aerobic phenotype in the ARS14 than before fistula installation. In conclusion, the rumen fistula surgery destroys the anaerobic environment of rumen, leading to differences in rumen microbial diversity and function, but the apparent digestibility and total VFA were not affected.